What is the role of occupational physicians in the workplace during the COVID-19 pandemic in Japan? A qualitative interview study - Yu Igarashi; Seiichiro Tateishi; Tomoko Sawajima; Kodai Kikuchi; Mika Kawasumi; Juri Matsuoka; Arisa Harada; Koji Mori (BMC, 2022)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic has had various impacts on businesses and workers worldwide. The spread of infection has been reported through cluster outbreaks in the workplace, and World Health Organization has emphasized workplace infection control measures. Occupational physicians (OPs) are expected to actively support employers' efforts to minimize the damage of the pandemic. However, there is little research on the role of these specialists during a pandemic. Clarification of the contributions of OPs to health and safety at the workplace in the COVID-19 pandemic would be beneficial to ensure that OPs can be effectively deployed in the next pandemic. Methods We employed semi-structured interviews and qualitative content analysis of the interview transcripts. Twenty OPs were selected as priority candidates from among 600 OPs certificated of the JSOH, and thirteen who met the eligibility criteria agreed to participate. The online interviews were conducted in November and December 2020 with thirteen OPs. We extracted meaning units (MUs) from interview transcripts according to the research question: "What was the role of OP in the COVID-19 pandemic?" and condensed and abstracted them into codes and categorized them. Validity was confirmed by additional 5 OPs interviews. Results A total of 503 MUs were extracted from the transcripts. These were abstracted into 10 sub-categories and two categories. Categories 1 and 2 dealt with "Role in confronting the direct effects of the pandemic" and "Role in confronting the indirect effects of the pandemic" and accounted for 434 (86.3%) and 69 (13.7%) MUs, respectively. These results were validated by another 5 interviews. Conclusion This study identified the role of OPs in Japan in the COVID-19 pandemic. The results showed that they made a wide range of contributions to the direct and indirect effects of the pandemic. We hope our findings will help OPs during future pandemics or other long-term emergency situations.